(untitled) (Research, Society and Development, 2022)
Objective: To know the perception of parturients about the importance of follow-up during labor and postpartum. Method: This is a descriptive exploratory study, with a qualitative approach, carried out in a public maternity hospital in Baixada Maranhense. The data were obtained through a semi-structured interview with 18 parturients, organized in the form of a textual corpus and analyzed with the IRaMuTeQ program. Trees of similarity were generated, they were interpreted and submitted to an analysis of thematic content. Results: Based on the analysis, four categories emerged: The importance of choosing a companion in the delivery room; The companion as a softener of the negative experiences in childbirth; The social support perceived in the presence of the companion during childbirth; Women’s view of the nursing team as a companion in the childbirth process. The faults expressed the need for the guarantee of having a companion, bearing in mind that all the deponents were unable to have the presence of a companion of their escort. Conclusion: This study presents the reports of women in the puerperium on the importance of follow-up during childbirth and the postpartum period and highlights the lack of assistance from prepartum to postpartum, these results converge on the need for related advances with access to information during pre-delivery in relation to their rights, as well as improvements by health establishments to receive follow-up.